SCN1A Mutation—Beyond Dravet Syndrome: A Systematic Review and Narrative Synthesis - Ding, Jiangwei; Li, Xinxiao; Tian, Haiyan; Wang, Lei; Guo, Baorui; Wang, Yangyang; Li, Wenchao; Wang, Feng; Sun, Tao (Frontiers in Neurology, 2021)
Background: SCN1A is one of the most common epilepsy genes. About 80% of SCN1A gene mutations cause Dravet syndrome (DS), which is a catastrophic epileptic encephalopathy. More than 1800 mutations have been identified in SCN1A. Although it is known that SCN1A is the main cause of DS and genetic epilepsy with febrile seizures plus (GEFS+), there is a dearth of information on other related diseases caused by SCN1A mutations. Objective: The aim of the present study is to systematically review the literature associated with SCN1A and other non-Dravet syndrome-related disorders. Methods: We searched PUBMED and SCOPUS for all published cases related to SCN1A gene mutations until October 20, 2021. The results reported by each study were summarized narratively. Results: The PUBMED and SCOPUS search yielded 2889 items. A total of 453 studies published between 2005 and 2020 met the final inclusion criteria. Overall, 303 studies on Dravet syndrome, 93 on GEFS+, three on Doose syndrome, nine on epilepsy of infancy with migrating focal seizures (EIMFS), six on West syndrome, two on Lennox-Gastaut syndrome, one on Rett syndrome, seven on nonsyndromic epileptic encephalopathy, 19 on hemiplegia migraine, six on autism spectrum disorder (ASD), two on non-epileptic SCN1A-related sudden deaths, and two on arthrogryposis multiplex congenita were included. Conclusion: Aside from DS, SCN1A also causes other epileptic encephalopathies, such as GEFS+, Doose syndrome, EIMFS, West syndrome, Lennox-Gastaut syndrome, and nonsyndromic epileptic encephalopathy. In addition to epilepsy, hemiplegic migraine, ASD, sudden death and arthrogryposis multiplex congenita can also be caused by SCN1A mutations.